Comparing ATA guidelines vs TI-RADS for evaluation of pediatric thyroid lesions. (January 2023) - Dunya, Gabriel; Dance, Logan; Grimmer, J. Fredrik
Abstract: Objective: To compare TI-RADS vs ATA guidelines for pediatric thyroid lesions based on ultrasound, in a retrospective study over 10 years. The primary outcome measure was sensitivity of both guidelines in diagnosing a thyroid malignancy on Fine Needle Aspiration (FNA) results. Methods: Retrospective data collection of all pediatric patients who had an FNA at the Primary Children's Hospital for thyroid lesions. Both guidelines were compared to determine which set of guidelines is most sensitive based on final outcome of pathology. Results: Seventy-seven patients were included in the study. All 77 underwent FNA as recommended by the ATA guidelines. 54.5% were benign, 22.1% were suspicious, and 23.4% were malignant lesions. Following the TI-RADS guidelines, 40.5% of these patients could have skipped the FNA. Using the ATA guidelines, all malignant lesions would have undergone FNA. However, using the TI-RADS guidelines, some patients with malignant lesions would have been ignored (5.6%) and some followed (22.2%) showing overall less sensitivity (75%). Conclusions: The ATA ultrasound guidelines for evaluation of thyroid nodules in children are more sensitive in screening for well-differentiated thyroid malignancy. Increased sensitivity is due in part to the size constraint within the TIRADS system. All providers who evaluate thyroid nodules in children should use the ATA pediatric guidelines to avoid missing smaller malignancies in children.